ANALISIS PROBLEMATIKA ANALISIS PROBLEMATIKA PEMBELAJARAN IPA BERBASIS E-MODUL DAN INKUIRI KOLABORATIF: STUDI KASUS PERSPEKTIF GURU DAN SISWA: ANALISIS PROBLEMATIKA PEMBELAJARAN IPA BERBASIS E-MODUL DAN INKUIRI KOLABORATIF: STUDI KASUS PERSPEKTIF GURU DAN SISWA - suci khoirani khoirani; Mery Berlian; Rian Vebrianto; Arinta Indah Ramadhani (Program Studi Tadris IPA IAIN Parepare, 2026)
In education, implementing learning is not as easy as putting all learning theories and media into practice. Therefore, the researcher aims to identify problems related to the implementation of learning theories and media. This research design is a case study. The methodology of this research uses mixed methods, in which quantitative data is strengthened by qualitative data. This study involved 5 science teachers and 25 fourth-grade students. This study used interviews, observation, and questionnaire instruments. Data were collected by directly going to the field and analyzed using descriptive statistics for quantitative data and analysis of interview results for qualitative data, so that the data obtained were comprehensive. The results of this study revealed that the main problems from the student perspective lie in the e-module design aspect (average score of 3.56), group dynamics (3.32), and memory retention (3.32). Meanwhile, from the teacher perspective, the most pressing problems are the burden of teacher guidance (3.20), student inquiry skills (2.80), and learning evaluation (2.80). Therefore, it can be concluded that there is a need to improve the e-module design, increase teacher scaffolding, and develop strategies to maintain students' conceptual understanding. so that it can be practically recommended for optimizing technology-based science learning in elementary schools.